2008
DOI: 10.1002/jcb.21778
|View full text |Cite
|
Sign up to set email alerts
|

The HspA2 protein localizes in nucleoli and centrosomes of heat shocked cancer cells

Abstract: The human HSPA2 gene, which belongs to the HSP70 family of heat shock genes, is a counterpart of rodent testis-specific HspA2 gene. Rodent genes are expressed mainly in pachytene spermatocytes, while transcripts of human HSPA2 gene have been detected in various normal somatic tissues, albeit translation of the messenger RNA into corresponding protein has not been yet unambiguously demonstrated, except for several cancer cell lines. The aim of our work, a first step in search for HspA2 function in cancer cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 40 publications
5
44
0
Order By: Relevance
“…However, anti-Hspa2 antibody used in this work was highly speciWc and showed no cross-reactivity with those Hsp70 proteins ( Fig. 1a; also Rosario et al 1992;Scieglinska et al 2008). Moreover, no unspeciWc binding of the antibody to proteins extracted from mouse organs was detected (Fig.…”
Section: Characterization Of Hspa2 Protein Expression By Western Blotmentioning
confidence: 84%
See 3 more Smart Citations
“…However, anti-Hspa2 antibody used in this work was highly speciWc and showed no cross-reactivity with those Hsp70 proteins ( Fig. 1a; also Rosario et al 1992;Scieglinska et al 2008). Moreover, no unspeciWc binding of the antibody to proteins extracted from mouse organs was detected (Fig.…”
Section: Characterization Of Hspa2 Protein Expression By Western Blotmentioning
confidence: 84%
“…However, in many others somatic tissues Hspa2 transcription was shown to be very low in rodents (Scieglinska et al 1997), but abundant in human (Bonnycastle et al 1994;Roux et al 1994). In addition, the expression of HSPA2 was also reported in several human cancer cell lines and primary cancers (Rohde et al 2005;Piglowski et al 2007;Scieglinska et al 2008).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…With regard to the HSPA family members HSPA1 [stress-inducible chaperone found to be expressed in primary tumors, but also with stress-independent expression in certain normal epithelial cells (Mangurten et al 1997;Trautinger et al 1995)] and HSPA2 [the expression of which was originally ascribed exclusively to certain testicular cell types (Huszar et al 2000;Son et al 1999), suggesting a role for HSPA2 in spermatid development/progression of spermatogenesis (Dix et al 1997;Govin et al 2006;Huszar et al 2000); however, an additional role in tumorigenesis has also been suggested (Piglowski et al 2007;Rohde et al 2005;Scieglinska et al 2008)] expression pattern have rarely been investigated in normal, non-stressed/pathological human tissues. Therefore, Scieglinska et al (2011) performed a thorough tissue-microarray based immunohistochemical study to collect new extensive data on the possible constitutive cell type-specific expression of the HSPA family members HSPA1 and HSPA2 in human somatic tissues, screening samples of 24 normal tissues derived from up to 11 donors.…”
Section: Moleculesmentioning
confidence: 94%